Investigation of High Energy Single Pulse Effect on Micro Arc Oxidation (MAO) Process on Aluminium - Yılmaz, Mustafa Safa; Şahin, Orhan (Avestia Publishing, 2019)
Micro Arc Oxidation (MAO) was applied by using high-energy anodic/cathodic pulses with various pulse durations. Anodic and cathodic pulse couples were kept at a constant voltage of 500 volts. Energy of each pulse increased with increasing duration of pulses. Since the aim of the present study was to investigate effect of pulse durations on MAO processing, other processing parameters such as duty cycle (8%), electrolyte temperature (25±5 °C), electrolyte composition (KOH, Na2SiO3.5H2O), process time (20 minutes), anodic pulse voltage, cathodic pulse voltage and chemical composition of substrate were all kept constant. Five different anodic and cathodic pulse durations were applied. Scanning electron microscope (SEM), indenter, profilometer, eddy current and X-ray diffractometer were employed to investigate the microstructure, hardness, surface roughness, coating thickness and phase distribution of the coatings. Varying of pulse duration occurred significant differences among coating specifications. Coating layers with thickness between 50-90 μm and surface roughness between 3.1-5.2 μm were obtained. The hardness of coating layers was between 800-2000 Vickers. Coatings consist of two sub-layers, inner dense layer and outer porous layer, which were a mixture of γ-Al2O3 and α- Al2O3.
Keywords: Aluminium; Coating; Micro Arc Oxidation; Surface Characterization